Heard on the Birdline, September 1-November 30, 2000 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (2000)
Summary of the Iowa Birdline update for September 1-November 30, 2000. Highlights of the update include exceptional sightings of a Pygmy Nuthatch, a Swallow-tailed Kite, a juvenile Parasitic Jaeger, and a family of three Whopping Cranes. Also of note was the extensive number and variety of fall gull sightings that were seen throughout the state. A fall Hawk watch resulted in some interesting observations, including 38 Mississippi Kites as well as large numbers of Prairie Falcons, Northern Goshawks, and Golden Eagles. Epson - sheet feed